COAL DUST CONTROLLER ON INDRAMAYU POWER PLANTS CONVEYOR LANE BASED IOT - Reza Yoga Diputra; Arief Marwanto; Suryani Alifah (Universitas Islam Sultan Agung, 2018)
The coal is combustion fuel of power plant which is located in Indramayu West Java. Power plant has produce coal dust during combustion process. Moreover, the residu of coal dust has potentially self combustion which damage or could explosived arround the environment. To addressing this situation, detection and controlling combustion dust is needed. To avoid this situation, a prototype devices which able to control combustion dust is proposed. The prototype has comprises of processing signal which controlling by Arduino microcontroller and sensed by MQ2 sensor for flammable gas and MQ135 for CO2 sensor, and Sharp GP2Y1010AU0F for dust sensor.These sensor are detected combustion dust, if the level more than set level then springkle will spray the water. The reading point value of sensors transmitted on to thingspeak IoT could server, which of sensor are consist of methane, gas, CO2, and dust. These value has monitored and able to conduct for controlling the combustion dust. The evaluation shows that the value of sensors are able to delivered as well and the relay as able to activated whenever level of combustion is above.